Trends in rheumatic fever: clinical aspects and perspectives in prophylactic treatments - Silva, Kattya Gyselle de Holanda E.; Barratt, Gillian; Oliveira, Anselmo Gomes de [UNESP]; Tabosa do Egito, Eryvaldo Socrates (Informa Healthcare, 2012)
Introduction: Rheumatic fever (RF), a systemic illness that may occur following Group A beta-hemolytic streptococcal (GABHS) pharyngitis in children, is a major problem in countries with limited resources. Because of its long track record and low cost, an injection of benzathine penicillin G (BPG) suspension every 3 or 4 weeks has been used as secondary prophylaxis. Despite its excellent in vitro efficacy, the inability of BPG to eradicate GABHS has been frequently reported.Areas covered: This work reviews the possible causes of failure, as well as the inconvenience of the current prophylactic treatment of acute RF and suggests a new pharmacotherapeutic system that could replace the current one.Expert opinion: RF is a major problem concerning only countries with limited resources and could be considered as a neglected disease. The dose regimen using BPG suspension results in failures, which could be avoided by the use of nanocarrier-based systems. To meet this ultimate goal, the research should be transposed from the laboratory scale to an industrial and clinical application level. This research should be conducted to produce a pharmaceutical dosage form that will be commercially available, consumed by and affordable for patients. However, health, environmental and socioeconomic hazards should be considered.
Keywords: benzathine penicillin G; microemulsion; nanotechnology; rheumatic fever